Strategies For Enhancing Arabic Speaking Proficiency Among Students In Government-Aided Religious Schools In Malaysia - Mohamed Shalikin, Nor Hadisah; Abdul Ghani, Mohammad Taufiq (Ijaz Arabi Journal of Arabic Learning, 2025)
Proficiency in Arabic has become a significant priority for pupils in Government-Aided Religious Schools, as it constitutes a fundamental objective of Arabic language education in Malaysia. Proficiency in this skill is essential and is evaluated during oral examinations. Obstacles to attaining this competency frequently stem from students' dispositions, inadequate pedagogical methods, and external influences. This study seeks to ascertain the levels of Arabic speaking competency and the tactics for mastering this talent that can be implemented, particularly by students and educators, with assistance from the surrounding environment. This study utilizes a qualitative methodology, including semi-structured interviews for data acquisition. A total of 35 students from government-aid religious Schools in peninsular Malaysia were chosen as responders by purposive sampling. The gathered data will undergo thematic analysis with Atlas.ti software. Research reveals three tiers of Arabic speaking skills among students: weak, moderate, and proficient. This study indicates that successful ways to develop Arabic speaking abilities encompass repetitive practice, environmental support, active engagement in extracurricular activities, background knowledge, and motivation. Therefore, Arabic speaking abilities must be refined to attain a proficient level of fluency using efficient and interactive mastery techniques, enhancing the capability of students to utilize Arabic successfully in everyday conversation and promoting reciprocal communication in the classroom.